Alternative Bypass Technique Using Radial Artery Graft between V3 Segment of Vertebral Artery and Middle Cerebral Artery: Technical Note - Ito, Yasuhiro; Maruichi, Katsuhiko; Nakayama, Naoki; Kobayashi, Hiroyuki; Tatezawa, Ryota; Shinada, Shinitirou; Terasaka, Shunsuke (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background There are some cases where a radial artery (RA) graft is needed for a high-flow extracranial to intracranial (EC-IC) bypass as the external carotid artery (ECA) cannot be utilized as a donor artery. In this report, we describe two cases of extracranial vertebral artery (VA) to middle cerebral artery (MCA) high-flow bypass using an RA graft with an artificial vessel as an alternative bypass technique.Methods The patient was placed supine with a head rotation of 80 degrees. After frontotemporal craniotomy, another C-shaped skin incision was made at the retroauricular region and the V3 portion of the VA was exposed at the suboccipital triangle. Prior to attempting the high-flow bypass, the superficial temporal artery (STA) was anastomosed to the M4 portion of the MCA as an insurance bypass. The RA graft was anastomosed to the V3 portion of the VA that traveled under the periosteum at the supra-auricular region through an artificial vessel. After RA-M2 anastomosis, an alternative EC-IC bypass, the V3-RA-M2 bypass, was achieved.Results Postoperative angiography demonstrated successful graft patency and no perioperative complications were observed in both cases.Conclusions In the cases where a high-flow bypass is required, the V3 portion of the VA is a suitable alternative proximal anastomosis site when the ECA is not a candidate donor. Furthermore, an artificial vessel shows satisfactory protection against graft complications.
Keywords: artificial vessel; high-flow bypass; radial artery graft; surgical technique; vertebral artery